(untitled) (Вісник: Міжнародні відносини, 2025)
Abstract Introduction. The Russian Federation’s full-scale invasion of Ukraine in 2022 marked a critical turning point in the European security landscape, prompting Sweden and Finland to abandon their longstanding policies of neutrality in favor of accession to the North Atlantic Treaty Organization (NATO). This strategic realignment has been accompanied by a notable intensification of Russian hybrid activity in Northern Europe. The resulting transformation of the regional security status quo presents NATO with novel challenges, underscoring the imperative for enhanced coordination mechanisms and deeper integration of the Nordic states into the Alliance’s strategic framework. Methods. The study employs a functional analysis to assess the implications of Russian hybrid operations for the Northern European states, a comparative method to synthesize and contrast the existing scholarly interpretations, and an examination of open-source materials and statistical data to construct an empirical basis for evaluating the scope and impact of Russian hybrid influence in the region. Results. The analysis delineates the evolving patterns and strategic objectives of Russian hybrid activities in Northern Europe following Sweden’s and Finland’s NATO accession. It further evaluates the Nordic states’ role in reinforcing the security architecture of NATO’s northeastern flank and identifies the key domains of vulnerability and potential countermeasures, with particular emphasis on the Baltic Sea region. Conclusions. The escalation of Russian hybrid warfare in Northern Europe post-2022 is not merely a reactive measure to geopolitical shifts but constitutes a calculated element of a broader long-term strategy aimed at undermining the Euro-Atlantic unity and degrading the collective defense capacity of NATO. The study finds that Russian hybrid operations seek to erode the political and military readiness of Nordic states, foster gradual regional destabilization, and weaken the cohesion of the transatlantic alliance. Instruments employed in such strategy include the critical undersea infrastructure sabotage, electoral interference, migration crises orchestration, disinformation campaigns, and the GPS signals jamming.